Woody plant phylogenetic diversity supports nature's contributions to people but is at risk from human population growth - T. Jonathan Davies; Olivier Maurin; Kowiyou Yessoufou; Barnabas H. Daru; Bezeng S. Bezeng; Ledile T. Mankga; Hanno Schaefer; Wilfried Thuiller; Michelle van der Bank (Conservation Letters, 2022)
Abstract The Tree of Life—phylogeny—provides a powerful tool for understanding the processes regulating life's diversity. Conserving the branches on the Tree of Life might also have practical benefits. Using a comprehensive phylogeny of southern African woody trees and shrubs, and structural equation modeling, we show that human population density correlates closely with not only the richness of woody plants in a region but also their evolutionary relatedness. Further, we demonstrate that more phylogenetically diverse species assemblages support a greater diversity of ecosystem goods and services. Our results suggest that people in Africa may gain material benefits from inhabiting regions that support high phylogenetic diversity of woody plants. However, the correlation between human population and woody plant diversity creates a tension between people and biodiversity, which could threaten the contributions to people provided by intact and phylogenetically diverse ecosystems.